Aggregation of heptanuclear [MII7] (M = Co, Ni, Zn) clusters by a Schiff-base ligand derived from o-vanillin: Synthesis, crystal structures and magnetic properties. (1st October 2019) - Gheorghe, Ruxandra; Andreea Ionita, Georgiana; Maxim, Catalin; Caneschi, Andrea; Sorace, Lorenzo; Andruh, Marius
Graphical abstract: Homometallic heptanuclear clusters with a wheel topology have been assembled using a Schiff base ligand resulted from the condensation reaction between o -vanillin and 2-methoxybenzylamine. Abstract: Three transition metal heptanuclear clusters, [Co7 L6 (μ3 -OCH3 )6 ](ClO4 )2 ·H2 O(1), [Ni7 L6 (μ3 -OH)6 ](ClO4 )2 ·4DMF (2 ), [Zn7 L6 (μ3 -OCH3 )6 ](ClO4 )2 (3 ), have been obtained using a new Schiff base ligand (HL) derived from o -vanillin and 2-methoxybenzylamine. The structures of1 –3 have been determined based on single crystal X-ray diffraction studies. They have similar wheel structures in which six metal ions locate on the rim with the seventh metal ion in the center. Complex3 exhibits luminescence in the solid state at room temperature. Variable-temperature DC and AC magnetic studies were carried out on polycrystalline samples of1 and2 . Compound1 shows an overall ferromagnetic coupling and absence of SMM behavior despite the observation of out-of-phase susceptibility in external applied field. The analysis of the magnetic data for compound2 emphasizes the interplay of ferromagnetic interactions between central and peripheral nickel(II) ions ( J 1 = −11.2 cm −1 ), and antiferromagnetic interactions between the peripheral nickel(II) ions ( J 2 = 9.6 cm −1 ); H = Σ J ij S i S j .